Genetic engineering of Saccharomyces cerevisiae for efficient expression and secretion of Erwinia pectate lyase and polygalacturonase - Laing, Elizna (Stellenbosch : Stellenbosch University, 2012)
Dissertation (Ph. D.) -- University of Stellenbosch, 1992.